Identity Crisis in the Era of Cultural Changes - Szumera, Grażyna (Folia Philosophica, 2024)
The problem of identity has only recently become the subject of research interest. There are many reasons why identity has become a much-debated issue; however, they all focus on the transformation of collective life in contemporary civilization, in which the bond between the individual and the community has changed significantly. The identity of the individual in traditional societies was not problematic. However, the change in self-identification is a hallmark of modernity as well as a harbinger of an individual’s identity crisis. It is possible to observe a decline in the authority of traditional cultural institutions and an expansion of consumer identity patterns. When analyzing changes in the cultural context of identity, one should be aware of the relevance of this dilemma. In modern societies, which have been subject to globalization processes, the previously preferred value hierarchies have fallen apart, and it is becoming increasingly difficult for individuals to choose their own identity.